2009
DOI: 10.1111/j.1468-3083.2009.03233.x
|View full text |Cite
|
Sign up to set email alerts
|

The hair follicle melanocytes in vitiligo in relation to disease duration

Abstract: The melanotic melanocytes were the first target of the disease process followed by the amelanotic melanocytes. Since the disappearance of the latter was inversely correlated with the disease duration, early treatment in vitiligo is advised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 10 publications
3
46
0
Order By: Relevance
“…Melanocytes in hair follicles seem to be more robust, so that normal hair colour often persists in the white patch [28]. Greying and eventual whitening of scalp and body hair in the condition of poliosis is not considered a form of vitiligo, but there may be some shared pathomechanisms; early greying of the hair can be seen in some vitiligo lesions [29]. New studies on the control of melanogenesis and constitutional skin colour point to roles for cytokines like SCF (stem cell factor), ET-1 (endothelin-1) and granulocyte macrophage colony stimulating factor [30].…”
Section: Melaninmentioning
confidence: 97%
See 1 more Smart Citation
“…Melanocytes in hair follicles seem to be more robust, so that normal hair colour often persists in the white patch [28]. Greying and eventual whitening of scalp and body hair in the condition of poliosis is not considered a form of vitiligo, but there may be some shared pathomechanisms; early greying of the hair can be seen in some vitiligo lesions [29]. New studies on the control of melanogenesis and constitutional skin colour point to roles for cytokines like SCF (stem cell factor), ET-1 (endothelin-1) and granulocyte macrophage colony stimulating factor [30].…”
Section: Melaninmentioning
confidence: 97%
“…Van den Boorn et al [218] expanded on all these findings in 2009: their study showed a prominent role for T-cells in vitiligo pathogenesis, being causative rather than just a consequence of other stimuli. Perilesional T-cells were easily identified in nine HLA-A2 + patients with progressive vitiligo, cultured and subjected to flow cytometric analysis using HLA-A2/peptide tetramers for tyrosinase-(369-377), gp100-(280-288), gp100-(209-217) and MART-1- (26)(27)(28)(29)(30)(31)(32)(33)(34)(35). A control antigen in the form of influenza virus-(58-66) was employed.…”
Section: Antigen-specific T-cellsmentioning
confidence: 99%
“…While active melanocytes can be detected by DOPA and immunohistochemical staining (such as antibody NKI-beteb), amelanotic melanocytes can only be detected by the latter. [50,51] Ultrastructural studies have shown degenerative changes in early lesions. [52] Nevus depigmentosus can also present diagnostic challenges.…”
Section: Graft Versus Host Disease (Gvhd)mentioning
confidence: 98%
“…Melanocytes are absent from 100% of white hairs. 115 ETIOLOGY Key points d The cause of vitiligo is unknown d The autoimmune hypothesis is the best supported theory d The neurohumoral, cytotoxic, and oxidative stress theories have moderate evidence d New theories focus on melanocytorrhagy and decreased melanocyte survival…”
Section: Associations and Syndromes Key Pointsmentioning
confidence: 99%